THERMOPLASTIC RESIN COMPOSITION - NAGATA KOSUKE; TSUNODA ATSUSHI (2022)
To provide a thermoplastic resin composition that has excellent heat resistance and flame retardancy, shows no change in color during molding residence, and prevents resin degradation in high-temperature and high-humidity conditions.SOLUTION: A thermoplastic resin composition contains a resin component composed of (A) a polycarbonate resin (A component) 1-99 pts.wt. and (B) a polyarylate resin (B component) 99-1 pt.wt. Relative to 100 pts.wt. of the resin component, the thermoplastic resin composition further contains (C) an orthophosphate compound (C component) 0.001-2 pts.wt., (D) a phenolic compound (D component) 0.001-2 pts.wt. and (E) a flame retardant (component E) 0.005-20 pts.wt.SELECTED DRAWING: None 【課題】耐熱性、難燃性に優れ、成形滞留時に変色が生じず、さらには、高温高湿環境下での樹脂劣化が抑制される熱可塑性樹脂組成物を提供する。【解決手段】（Ａ）ポリカーボネート樹脂（Ａ成分）１～９９重量部および（Ｂ）ポリアリレート樹脂（Ｂ成分）９９～１重量部からなる樹脂成分１００重量部に対し、（Ｃ）正リン酸エステル化合物（Ｃ成分）０．００１～２重量部、（Ｄ）フェノール系化合物（Ｄ成分）０．００１～２重量部および（Ｅ）難燃剤（Ｅ成分）０．００５～２０重量部を含有することを特徴とする熱可塑性樹脂組成物。【選択図】なし